Harmonic Analysis for High-Speed Rail Installation 132kV - Fadzil, Muhammad Nasrullah; Mohd Ariff, Mohd Aifaa (Evolution in Electrical and Electronic Engineering, 2023)
The purpose of this paper is to simulate an AC traction circuit with an AC locomotive load. It also investigates current and voltage distortion in the power system supply as a result of harmonic analysis. The system mentioned before was studied for harmonics analysis of a projected 132kV high-speed rail installation. The MATLAB/SIMPOWER system is used to simulate the major components of the electric traction system for harmonic analysis. In addition, a mathematical model of the supply network is being built to quantitatively assess voltage distortion at different buses. This system depicts a study of the effect of a harmonic enhancement filter on AC traction linked to an AC locomotive load. Accordingly, the simulation result at stages of speed at 25%, 50%, 75%, and 100% the value of total harmonic distortion (THD) for voltage is 5.05% and a THD for current is 57.50% in the worst scenario. Next the simulation result at full cycle without passive filter, the result a THD for voltage is 5.58% and a THD for current is 55.53%. It also has a worst result for this simulation. Lastly the simulation result at the full cycle with passive filter, the value of THD for voltage is 0.62% and a THD for current is 0.77%, which are below IEEE 519 standard limits and TNB standard. This shows power quality and EMC improvement of the traction power supply system.